Assessment of suitability of ber (Ziziphus mauritiana L.) cultivars for value addition through dehydration technology - Das, U; Nidoni, U R; Kurubar, A R; Prasad, S S; Balaji, M (Plant Science Today, 2025)
This novel experiment assessed the suitability of twelve Indian jujube (Ziziphus mauritiana L.) cultivars for value addition through dehydration technology. Fresh fruit samples were collected randomly from the plants and subjected to dehydration. Five qualitative characters such as total soluble solids (TSS), pH of fruit pulp, moisture content, ascorbic acid content and phenol content were analyzed along with organoleptic evaluation of fresh and dehydrated ber cultivars. Significantly higher TSS among fresh ber was found in Chhuhara (23.96 °Brix) and dehydrated ber was in Sanaur-2 (29.91 ° Brix). The highest pH among the fresh and dehydrated cultivars was recorded in Illaichi (4.73), followed by Dandan (4.70). The highest ascorbic acid content was recorded in fresh Seb (108.73 mg/100 g of fresh fruit) and dehydrated Kadaka (58.55 mg/100 g of dry fruit pulp). Significantly, the highest phenol content among fresh and dehydrated ber was in Seb 219.40 mg/100 g of fresh fruit pulp and 236.24 mg/100 g of dry fruit pulp, respectively. In the organoleptic evaluation, Kadaka ranked first, retaining a high ascorbic acid content even after dehydration. Based on the present study, Kadaka appears to be the best cultivar for dehydration, followed by Seb and Gola.